(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Cloud computing has revolutionized the IT industry by offering scalable and on-demand resources under a pay-as-you-go model. However, the same flexibility that makes cloud computing attractive also introduces challenges in managing costs effectively. Cloud Cost Management (CCM) focuses on monitoring, analyzing and optimizing expenditure to achieve an ideal balance between performance and affordability. This paper reviews existing cost management strategies, techniques, and tools used across different cloud environments. It highlights traditional budgeting and monitoring methods, advanced optimization models using machine learning, and automation through FinOps practices. There view also identifies current challenges such as complex pricing structures, lack of cost visibility in multi-cloud environments, and unpredictable billing patterns. Finally, the paper discusses emerging trends and future research directions aimed at intelligent and sustainable cost optimization in cloud ecosystems.